Finite-Time Consensus of Networked Multiagent Systems with Time-Varying Linear Control Protocols. (11th May 2016) - Wen, Jiayan; Wang, Chen; Luo, Wenguang; Xie, Guangming
Abstract : Finite-time consensus problems for networked multiagent systems with first-order/second-order dynamics are investigated in this paper. The goal of this paper is to design local information based control protocols such that the systems achieve consensus at any preset time. In order to realize this objective, a class of linear feedback control protocols with time-varying gains is introduced. We prove that the multiagent systems under such kinds of time-varying control protocols can achieve consensus at the preset time if the undirected communication graph is connected. Numerical simulations are presented to illustrate the effectiveness of the obtained theoretic results.